Empathy and professional support via relate-to-self in post-observation meetings. (June 2023) - Lewis, Kristina B.; Wagner, Santoi
Abstract: Learning to teach is an emotional process for novice teachers. Mentors must provide both emotional and professional support to teachers in contexts such as post-observation meetings. In this study, we focus on one practice in expressing empathy, which we refer to as relate-to-self tellings, that mentors can do in response to teachers' problem-tellings. We highlight how relate-to-self tellings can both substantiate claims of understanding by demonstrating a similarity between the mentor and teacher in terms of shared experience and normalize problems to be viewed as typical or expected. We also consider how such relate-to-self tellings can work to provide or ground professional support, such as advice. We extend the research on delineating empathy as an interactional achievement, specifically within the institutional context of post-observation meetings within teacher education.